Conflict behavior in show jumping horses: A field study - Jastrzebska, E.; Wolska, A.; Minero, M.; Ogluszka, M.; Earley, B.; Wejer, J.; Gorecka-Bruzda, A. (Journal of Equine Veterinary Science, 2017)
Highlights: •Equine behavioral and physiological responses to show jumping were studied. •Horses with a greater number of faults showed a greater frequency of conflict behavior. •Horses with a greater number of faults had a greater salivary cortisol concentration (SCC). •Transportation prior to competition increases SCC.